Critical masculine and feminine norms in sustainable municipal transport policies and planning - Kronsell, Annica; Dymén, Christian; Rosqvist, Lena Smidfelt; Stepanova, Olga; Winslott Hiselius, Lena (Journal of Environmental Policy and Planning, 2023)
Transport planning has historically been dominated by masculinity norms with minimal attention to sustainability, but these norms are challenged. Our analytical framework explores municipal solutions to sustainable transport that go beyond traditional norms and advances knowledge on how gendered sustainability norms are articulated in municipal transport policies and planning documents. The article investigates whether masculine and feminine norms on sustainability affect transport planning and if they are concretely expressed in transport solutions in planning and policy documents in Swedish municipalities, considered high achievers in sustainable transport. The article also observes gender representation and political affiliation related to gender sustainability norms. Our results show that all municipal committees that handle transport planning adhere to masculine and feminine sustainability norms but that there are significant differences in the content of the policies. Our results do not verify a relation between norms and the representation of men and women in the transport committees, we find evidence of divergences between masculine and feminine norms in relation to political ideas.
Keywords: critical masculinities; eco-femininities; Gender norms; municipalities; sustainability; transport sector